A feasibility study Paper for iron, fold, storage: The versatile ironing brand - Acuman, Maria Paula B., Balisi, Joelyn V., Bermundo, Jenna Mae V., Estopace, Abegail E., Vargas, Antoneth T. 4 0 16; 5 (2024)
Abstract This paper aims at establishing the market feasibility of this concept and the practicality of using Flexiboard as an ironing board that has been invented and designed by AJP Corporation. As an appealing household product, Flexiboard is versatile, durable, and fashionable to cater for the changing demands of urban homes and small-scale enterprises. The assessment focuses on aspects of competitiveness, technology, management, financial and socio-economic performance of a product. It analyses the market and examines the need for storage and space-saving products used in households connected with middle-income users which is supported by the current urbanization and shift in preferences. Technical feasibility deals with following a specific manufacturing procedure, proper planning of the physical plant and implementing various quality control features that produce superior products. Management at the Company Headquarter level along with implementation of sound policies ensures the leadership of the organization financial management and planning re-emphasizes growth through efficient cost control and forecasting of income. Socio-economic benefits including employment opportunities, domestic economy impact and sustainability. The ability to offer affordable products, product quality, appealing and unique ideas, product advertising like focused on customer based ads, internet promotions, direct mail among several others boosts Flexiboard's market appeal. Consequently, issues such as competition and first brand association are areas of concern captured through the study findings that depicts how it is possible for Flexiboard to become a feasible and impactful venture if the given recommendations are to be strategically applied in the insecure household appliance industry.
Feasibility Study: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2